Higher Absolute Lymphocyte Counts and Lower Des‐γ‐Carboxyprothrombin Levels After Treatment Initiation Are Associated With the Clinical Efficacy of Tremelimumab Plus Durvalumab Combination Therapy for Hepatocellular Carcinoma - Yuta Inoue; Yoshihiko Yano; Saeko Kushida; Seiya Hirohata; Seitetsu Yoon; Eiichiro Yasutomi; Hirotaka Hirano; Soo Ki Kim; Ryutaro Yoshida; Yoshihide Ueda; Kenji Momose; Hiroki Hayashi; et al. (JGH Open)
ABSTRACT Background and Aims Tremelimumab plus durvalumab (Dur/Tre) combination therapy is now a first‐line systemic therapy for advanced hepatocellular carcinoma (HCC). Because systemic therapy is not effective in some patients, it is clinically important to identify factors that could predict the response to treatment at an early stage. We investigated the factors associated with the response to Dur/Tre for advanced HCC in a clinical setting. Methods Seventy patients (median age 74 years; 61 men) who received Dur/Tre between March 2023 and September 2024 were analyzed. We examined the factors associated with the treatment response, including pretreatment factors and factors early in treatment. Results The median treatment duration was 77.5 (interquartile range [IQR] 28–187) days. The overall response and disease control rates were 25.8% and 58.1%, respectively. The median (IQR) progression‐free survival (PFS) and overall survival (OS) were 82 (61–133) and 415 (337–NA) days, respectively. Multivariable analysis revealed that higher absolute lymphocyte count (ALC) and lower des‐γ‐carboxyprothrombin (DCP) levels were significantly associated with PFS. Receiver operating characteristic curve analysis showed that the cutoff value for ALC after 4 weeks of treatment in relation to clinical efficacy was 1125/mm3. A log‐rank test using the Kaplan–Meier method showed that OS was significantly longer in patients with ALC above the cutoff and in patients whose DCP levels decreased after starting treatment. Conclusion Higher ALC and lower DCP levels after treatment initiation were associated with the clinical efficacy of Dur/Tre for advanced HCC.